FACTORS AFFECTING CONSUMER BEHAVIOR IN BUYING DECISION OF SUZUKI ERTIGA CAR IN CILEGON CITY, BANTEN - Ditra Krahara, Yuwan; Mulyowahyudi, Alugoro (Dinasti Publisher, 2021)
This study aims to analyze the factors that influence consumer behavior in the decision to purchase a Suzuki Ertiga car in Cilegon City Banten. The population in this study were customers in the city of Cilegon who bought a Suzuki Ertiga with 200 participants. Methods of data analysis using the Structural Equation Model-Partial Least Squares (SEM-PLS). The software that is used to process and analyze data obtained from this study is the Smart PLS version 3.3.2. The results of the study found that Product Quality, brand awareness and promotion had a positive and significant effect on purchasing decisions.